Cannabis smoking increases the risk of suicide ideation and suicide attempt in young individuals of 11–21 years: A systematic review and meta-analysis. (September 2022) - Fresán, Ana; Dionisio-García, Diana María; González-Castro, Thelma Beatriz; Ramos-Méndez, Miguel Ángel; Castillo-Avila, Rosa Giannina; Tovilla-Zárate, Carlos Alfonso; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Genis-Mendoza, Alma Delia; Nicolini, Humberto
Abstract: Background: Cannabis is the most frequently consumed drug around the world. Its use has been associated with increased suicide behaviors; nonetheless, the association of cannabis smoking and suicide behaviors in adolescents has not yet been established. The aim of this systematic review and meta-analysis was to evaluate the risk of suicide attempt, suicidal ideation or suicide planning in individuals of 11–21 years of age who smoke cannabis. Methods: We performed an online searched using PubMed, EBSCO and Science Direct databases, up to July 2021. We calculated odds ratio with 95% confidence intervals to evaluate the association between suicide attempt, suicidal ideation or suicide planning and cannabis smoking in individuals of 11–21 years of age. Results: Twenty studies reported suicide attempts in 34, 859 young individuals, suicidal ideation in 26, 937 individuals, and suicide planning in 9054 young individuals. We found an increased risk of suicide attempt in cannabis smokers than in non-cannabis users (OR: 2.33; 95% CI: 1.78–3.05; Z p value; <0.0001; I 2 = 97.12%), as well as a significant association between cannabis smoking and suicidal ideation (OR: 2.04; 95%CI: 1.64–2.53; Z p value: <0.001; I 2 : 94.88) and suicide planning (OR: 1.674; 95% CI: 1.554–1.804; Z p value: 0.000; I 2 : 92.609). Subgroup analyses showed that American teens have an increased risk of suicidal ideation; the meta-regression analysis revealed that age was negatively associated with the risk of suicide attempt. Conclusions: This meta-analysis shows that cannabis smoking increased the risk of suicide attempt, suicidal ideation and suicide planning in young individuals of 11–21 years of age. The high risk of suicide behaviors could vary depending on the population studied; therefore, more studies are necessary to corroborate the risk of presenting suicide behaviors in individuals of 11–21 years of age who smoke cannabis.